Penerapan Model Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Hasil Belajar Matematika pada Siswa Kelas V SDI Blidit Kabupaten Sikka - Theresia Anisensia; Gregorius Sebo Bito; Marselina Wali (Program Studi PGSD Universitas Flores, 2020)
The objectives of this study are: 1) to know the implementation of cooperative learning model of STAD type in mathematics learning in class V students in SDI Blidit, Waigete, Sikka Regency, 2) to find out the improvement of students' learning outcomes after applying cooperative learning model of STAD type on mathematics learning in class V students in SDI Blidit, Waigete, Sikka Regency. This research is a type of Classroom Action Research (CAR) by using a qualitative approach. The subject in this study was the V-grade SDI Blidit student, numbering 20 students. The techniques of data collection in this study were observation, interview, test and documentation. Based on the results of the data analysis and the discussion of the results can be concluded that the results of the study of class V students in mathematics after implementation the cooperative learning model of STAD type in cycle I has not reached the complete learning. It can be seen from the number of students who reached the KKM or minimal completeness criteria is 6 people (60.5%) of 20 students, while in cycle II has undergone an increase by an overall percentage of 86%. Teacher and student activities also increased from cycle I to cycle II; (56.15%) in cycle I and (84.61%) in cycle II with its criteria is very good. While the student activity cycle I (50%) and cycle II (87.7%) are in excellent criteria. Based on the results of the interviews, it can be concluded that students are motivated when learning materials are implemented using the STAD type Cooperative learning model.